Theoretical Framework Over Vivid Facets on Student’s Intention To Payback Education Loan in India (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Education loan is a magical solution to address the education financing crises. It bridges the gap between accessibility and sustainability but incidents of defaults in the repayment of education loan are on rise. The Present study covers various theories has been thoroughly analysed to understand the factors which influence the intention of student to repay the education loan. A comprehensive theoretical framework has been designed by reviewing various literatures on student intention. This structural framework encompasses - Attitude to repay or default of education loan, Integrity, Parental influence, awareness of loan agreement, Willingness to invest in educational plans, Student’s characteristics, Financial ability to pay and student’s priority from Theory of reasoned action, Theory of Planned behaviour, Theory of human capital and Theory of ability to pay. In this research study, all efforts have been made to determine the possible linkage between factors that influence student’s intention to pay or default the education loan.